PENGARUH KOMPETENSI PROFESIONAL, KEPEMIMPINAN TRANSFORMASIONAL DAN KOMUNIKASI INTERPERSONAL TERHADAP KINERJA GURU DENGAN MEDIASI KEPUASAN KERJA (Studi Pada Guru SMP Negeri di Kecamatan Boja) - 11.52.02.0114, Mahrudi (Jurnal Mahasiswa Pasca Sarjana, 2013)
This study is aimed to examine and analyze the influence of competency profesional, leadership transformasional, and communication interpersonal on improving job performance mediation job satisfaction to teacherâs goverment yunior school in the Boja.The population taken in this study is all the permanent teachers civil servant in teachers goverment yunior school in the Boja with 110 respondents. The method used for examining the data includes validity test with factor analysis and reliability test using the Cronbachâs Alpha formula, double regression analysis, signification test and determination of coefficient to prove the truth of hipotesa, as well as the mediation test.the result of the study showed that (1) Professional competence positively influences and significant to the job performance sebesar 15,7 %, (2) Professional competence positively influences and significant to the job satisfaction19,8 % (3) Leadership Transformasional positively influences and significant to the teacherâs performance,sebesar 10,6 % (4) Leadership Transformasional positively influences and significant to the teacherâs performance, sebesar 51,2% (5) Communication interpersonal positively influences and significant to the teacherâs performance,73,9% , (6) ) Communication interpersonal positively influences and significant to the job satisfaction, sebesar 16,7 %(7) Job satisfaction influences and significant to the teacherâs performance sebesar 16,1 %.(8) Professional competence is mediated job satisfaction on teacher performnce. , (9) Leadership Transformasional is mediated job satisfaction on teacher performance.(10) Communication Interpersonal is mediated job mediated job satisfaction on teacher performance. Key words : Competency Profesional, Leadership Transformasional, Communication Interpersonal, Job Satisfaction, and Teacherâs Performance